Interfaith dialogue: seven key questions for theory, policy and practice - Orton, Andrew (Religion, state & society, 2016)
Interfaith dialogue is increasingly being recognised by governments across Europe as crucial to developing cohesive communities. This article critically analyses approaches for developing strategies to promote interfaith dialogue between individuals and/or organisations within civil society. It does this by drawing on a series of theoretical questions concerning those who are involved (and missing), what the dialogue is for, and how the dynamics of participation and representation are handled. In the process, the article considers the conditions, spaces, processes, relationships and understandings of identity that can enable successful interfaith dialogue, and how these might be developed in ways which address the issues raised. The original theoretical analysis presented in this article is supported by examples from the author's cumulative research with policymakers and practitioners across Europe since 2004.